Pengembangan Sistem Informasi Public E-Marketplace pada PT XYZ - Agus Sulaiman (ULTIMA InfoSys, 2015)
In this modern era, internet technology and information system are very crucial in helping people or companies running their business. The latest technology allows people to buy and sell online using an electronic system that is known as e-commerce. Admittedly, many people still feel insecure when doing transactions in cyberspace due to the fact that fraud often occurs between buyers and sellers. To overcome this downside, this study aims to develop an online application that will provide a secure environment for sellers and buyers to transact named public e-marketplace. This system has several features. First, features for seller: registration functionality, login functionality, products management, transactions management, profile management. Second, features for buyer: registration functionality, login functionality, searching functionality for suppliers and products, transaction management, payment confirmation, Profile management. Third, features for admin: ability to view the status of the account, ability to update the account activation, payment verification, delivery verification, refund verification. For the security of the system used HTTPS on a page and form URL, SSL or TLS, Captcha secure word and password encryption. This application will be developed with ASP.NET technology, using SQL Server to store its database and Internet Information Service (IIS) as its web server. Index Terms - e-marketplace, information system, security.